Economic diversification of rural households in the Republic of Macedonia - Gjosheva Kovachevikj, Marija; Gorgievski, Blagoja (University of East Sarajevo, Faculty of Agriculture, Republic of Srpska, Bosnia, 2016)
Sustainable rural development is vital to the national social and economic situation of the Republic of Macedonia since 43% of the population lives in rural areas, which make up 86.7% of the total territory. Most of the rural households are engaged in agriculture (primarily family farms) and very small portion in other activities. Agricultural wages tend to be significantly lower than other sectors and almost half of the labour force is consisting from unpaid family members. To that end, modern understanding of rural development exceeds the concept that agriculture is the only non-urban element of territorial areas and move to a broader concept that refers to all resources of the territory and its entire economic structure: natural and human resources, crafts, small industrial facilities, tourism, recreation etc. The goal of this paper is to review the new direction of rural development in Macedonia - income diversification, focused on contribution of non-farm activities to total rural household incomes. The methods of descriptive statistics of data analysis were used to process official data for incomes, from State Statistical office. The findings demonstrate that number of rural households with incomes from non-agricultural activities accounts only 16%, with highest proportion (69%) of households with share of only up to 10% of non-farm incomes in total turnover. Policy for strengthening of the conditions for development of the rural diversification activities, as one of the tool for economic stability of rural households is recommended to be one of the highest governmental strategic priorities for rural development.
/
Keywords: rural development, income, diversification